2020
DOI: 10.1007/s40272-020-00407-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Reported Pediatric Medication Errors in Northern Ireland and Use in Quality Improvement

Abstract: BackgroundTo protect children from harm, clinicians, educators, and patient safety champions need information to direct improvement efforts. Critical incident data, often disregarded as a source of evidence because under-reporting makes them an inaccurate measure of error rates, could provide this. AimOur aim was to identify key targets for pediatric healthcare quality improvement. The objective was to evaluate the types, characteristics, and areas of risk within reported medication errors in pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…33 Recent estimates also highlight this issue, whereby administration errors accounted between 42.5% and 54% of pediatric medication errors. 14,15 Of interest, Kaushal et al found that harmful errors occurred most commonly at the drug administration stage by parents. 34 Interventional studies in hospital medication administration errors explored barcode medicine administration, electronic prescribing, education and training, use of smart pumps, and standard concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Recent estimates also highlight this issue, whereby administration errors accounted between 42.5% and 54% of pediatric medication errors. 14,15 Of interest, Kaushal et al found that harmful errors occurred most commonly at the drug administration stage by parents. 34 Interventional studies in hospital medication administration errors explored barcode medicine administration, electronic prescribing, education and training, use of smart pumps, and standard concentration.…”
Section: Discussionmentioning
confidence: 99%
“…10 Patterns of medication errors in pediatrics are understudied in the hospital and community settings. 14,15 Besides, using information from studies conducted on adults may be of limited value, since medication errors most likely differ between the two populations. 16,17 Exploring specific patterns of medication errors in pediatrics compared with adults could enhance our understanding of this complex problem in pediatrics and inform targeted efforts to enhance patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…safety guidance and research that aimed to reduce medication errors and related adverse drug events across different healthcare settings [5,9,[17][18][19].…”
Section: Key Pointsmentioning
confidence: 99%
“…Medication-related safety incidents are commonly reported as the most frequent incident type in hospitals and may be more likely to cause harm in children than in adults [1,2]. The risk of experiencing these incidents may be greater for neonates and children admitted to intensive care units (ICUs) than for those on general wards because of factors such as the use of medicines associated with a high risk of harm, complicated and severe illnesses, complex weightbased dosing calculations, and heavy staff workload [3][4][5]. In addition, neonates and children admitted to ICUs may be pre-verbal or sedated, and this will affect their ability to prevent errors themselves [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation